Pendampingan Pemeliharaan Drainase di Sungai Lekso Kota Blitar - Santi Sari; Nur Latifah Khomsiati; Dini Almira (Politeknik Penerbangan Indonesia Curug, 2022)
Drainage on the Lekso River in Blitar City is experiencing various problems, such as clogged channels, damage to infrastructure, and accumulation of garbage. Based on these problems, community service activities were carried out with the aim of assisting Drainage Maintenance on the Lekso River, Blitar City. The method used in this service is identification of drainage problems and needs through field surveys and consultations with relevant authorities and outreach to the community regarding the importance of maintaining good drainage and environmental management. As a result of this community service, the community receives training and education assistance for the community regarding proper drainage maintenance techniques, such as channel cleaning, infrastructure repair, and waste management. In addition, the local community carried out drainage cleaning and repair activities together with the guidance and supervision of the community service team.